OPTIMIZING CUSTOMER SATISFACTION THROUGH RELATIONSHIP MARKETING: A CASE STUDY OF PT PEGADAIAN MAMUJU BRANCH - Ismayani Ismayani; Muchtar Muchtar; Iwan Adinugroho (Jurnal Ekonomi, 2023)
This study investigates the relationship between Relationship Marketing (RM) and customer satisfaction at PT Pegadaian Mamuju Branch. Analyzing data collected from a sample of 50 customers, the research found a significant correlation (r = 0.332) between RM and customer satisfaction. The results align with Lovelock's view that satisfaction is shaped by customer experiences. While acknowledging the influence of other factors like service quality, this study highlights the crucial role of RM in enhancing customer contentment. The findings suggest that PT Pegadaian's efforts in fostering customer relationships, personalized experiences, and trust have positively impacted satisfaction levels. This underscores the importance of effective RM strategies in fostering loyalty, potential sales growth, and overall business advancement.